UNDERSTANDING STUDENTS' CONCEPT OF SALT HYDROLYSIS MATERIAL AT THREE LEVELS OF CHEMICAL REPRESENTATION AT SENIOR HIGH SCHOOL (SMAN) 2 PADANG PANJANG, WEST SUMATERA - DELPIMA SUHITA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The low understanding of students at SMAN 2 Padang Panjang about salt hydrolysis. This phenomenon affects their learning outcomes which can be seen in the incomplete KKM scores. They should be able to clearly explain the hydrolysis of salts in three levels of chemical representation which include the macroscopic level, the submicroscopic level and the symbolic level. To overcome this, it is necessary to conduct an analysis in order to know the disclosure of students' competence about the material. This study aims to analyze students' conceptions of salt formed from a strong acid and a strong base, a weak acid and a strong base, a strong acid and a weak base and the pH formed. This is a descriptive research. The data collection technique is by using tests. Open-ended questions were used in this study, which consisted of eight questions. Each question consists of three parts, namely the macroscopic level, the submicroscopic level, and the symbolic level. Students' answers from the test were classified into five categories: complete conception, incomplete conception, alternative conception, no conception and no response. The analysis shows that the percentage of students' understanding of the complete concept category at the submicroscopic level is the lowest. However, students' understanding at the macroscopic and symbolic levels is better than at the submicroscopic level.